Anemia in Pregnancy Based on Rural and Urban Areas - Catur Wulandari; Pratiwi Hariyani Putri; Anugrah Linda Mutiarani; Farah Nuriannisa; Farda Jamalia Hisbullah; Farah Nur Laily Mabruroh; Jauharotul Lu'luah; Miftakhul Solekha (Jurnal Kesehatan Masyarakat, 2025)
From 2013 to 2018, the proportion of anemia in pregnant women in urban and rural areas increased from 37.1% to 48.9%. This study aims to analyze the differences in determinants of anemia in pregnancy based on place of residence. Research was conducted in 2024. The research sample in rural areas was 39 pregnant women with anemia, and in urban areas was 31 pregnant women with anemia. Ratio scale data, including nutritional intake, is tested for normality with the Kolmogorov-Smirnov test, then tested using the t-independent test. Other variables are tested using the Mann-Whitney test. Regarding the various determinant factors studied, including the age of pregnant women, nutritional status, and gravida status, there is no significant difference (p-value > 0.05) in pregnant women with anemia in rural and urban areas. There is a significant difference (p-value < 0.05) between nutritional knowledge, food expenditure, and nutritional intake in pregnant women with anemia in rural and urban areas. Based on the determinant factors of anemia in pregnancy studied, food expenditure, nutritional knowledge of pregnant women, protein, iron, and vitamin C intake in pregnant women with anemia in rural and urban areas differ significantly.